High-intensity functional training with an adequate and carbohydrate-restricted hypocaloric diet promotes weight loss and cardiometabolic improvements - Leite, Marina de Macêdo Rodrigues; Grigoletto, Marzo Edir da Silva; Chagas, Bárbara Lúcia Fonseca; Machado, Ana Carolina Santos Barbosa; Vasconcelos, Alan Bruno Silva; Silva, Danielle Goes da; Mendes-Netto, Raquel Simões (ABCS Health Sciences, 2023)
Introduction: Excess body weight and its comorbidities represent a major public health issue. Interventions based on diet and exercise have not only been shown to promote weight loss, but also improve overall health, including cardiovascular health. Objective: This study aimed to evaluate the effects of a 12-week hypocaloric low-carbohydrate (CHO) diet coupled with high-intensity functional training (HIFT) on the cardiometabolic risk of overweight adults. Methods: This is a randomized controlled trial. A total of 31 overweight adults participated in this study, divided into two groups based on the dietary intervention: reduced-CHO (R-CHO, ≤130 g/day; n=15) and adequate-CHO (A-CHO, >130 g/day; n=16). The cardiometabolic risk was assessed using lipidaemic, insulinemia, and glycaemic parameters. A two-way ANOVA with Bonferroni post-hoc test was utilized to evaluate the effects of the intervention. A p-value < 0.05 was considered statistically significant. Results: Participants from both groups displayed decreased low-density lipoprotein, very-low-density lipoprotein, total cholesterol, and triacylglycerol concentrations, as well as the number of risk factors for the metabolic disease after 12 weeks. The high-density lipoprotein (HDL) cholesterol concentration of both groups increased after 12 weeks, however, the result of the intragroup analysis revealed that a significant increase was only observed in the participants from the A-CHO group. Conclusion: Reduced or adequate CHO intake was both found to be effective in reducing cardiometabolic risk. However, improvements in HDL and final cardiometabolic classification risk indicated that CHO adequacy in the diet might be a better strategy associated with caloric restriction and HIFT.